Cardiac tissue-derived extracellular matrix scaffolds for myocardial repair: advantages and challenges. Issue 4 (22nd April 2019) - KC, Pawan; Hong, Yi; Zhang, Ge
Abstract: Decellularized extracellular matrix (dECM) derived from myocardium has been widely explored as a nature scaffold for cardiac tissue engineering applications. Cardiac dECM offers many unique advantages such as preservation of organ-specific ECM microstructure and composition, demonstration of tissue-mimetic mechanical properties and retention of biochemical cues in favor of subsequent recellularization. However, current processes of dECM decellularization and recellularization still face many challenges including the need for balance between cell removal and extracellular matrix preservation, efficient recellularization of dECM for obtaining homogenous cell distribution, tailoring material properties of dECM for enhancing bioactivity and prevascularization of thick dECM. This review summarizes the recent progresses of using dECM scaffold for cardiac repair and discusses its major advantages and challenges for producing biomimetic cardiac patch.